Political events during the reign of Mirza Muhammad Wali Khan Sepahdar Azam Tengabani 30 September 1909-11 July 1910 - الجبوري علي إسماعيل زيدان; الغرباوي سناء حسن محي (Tasnim International Journal for Human, Social and Legal Sciences, 2023)
The constitutional revolution in Iran represented one of the most important revolutions in the history of the Middle East region against the tyranny of the absolute power represented by the rule of the Qajar state، and a bright page from the pages of modern Iranian history، after the interim government that ruled the country for about a month and a half in Iran، several Iranian governments were formed as Muhammad Wali took over Khan Subahdar Azam Takabani headed the first government on September 30، 1909، in addition to his position as Minister of War، after which his ministry began to lose part of its vitality and popularity، so its head took advantage of the opening of the Council on November 15، 1909 and announced his resignation from his position at its opening ceremony، but the Council and its members، in agreement with They decided to re-assign him to form his ministry for the second time. The government of Sepahdar Azam the second faced three problems. The first was the continued refusal of tsarist Russia to withdraw its forces from Iran. The second problem was the financial crisis that the government was exposed to. The third problem was the emergence of political parties that began to struggle with each other in order to impose their will on the stage of political events. Despite the efforts made، the government of Sepahdar Azam could not provide complete centralization of the state، in addition to the tense atmosphere between Sepahdar Azam and the deputies of the Council، which prompted him to submit his resignation on July 12، 1910، so that an agreement was reached between the members of the Shura Council to form a coalition government between the leaders of the Bakhtiaris known Democrats.